2014
DOI: 10.1186/2049-6958-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular lung water and pulmonary arterial wedge pressure for fluid management in patients with acute respiratory distress syndrome

Abstract: BackgroundExtravascular lung water (EVLW) is a sensitive prognostic indicator of pulmonary edema. Thus, EVLW may be an advantageous method of fluid management. This study aims to evaluate the outcomes of using EVLW and pulmonary artery wedge pressure (PAWP) as strategies for fluid management in patients with acute respiratory distress syndrome (ARDS).MethodsTwenty-nine patients were randomly divided into the EVLW and PAWP groups. The survival rate, ICU (Intensive Care Unit) length of stay, duration of mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…The use of random sequence generation and allocation concealment [19][20][21][22]25] and the risk of reporting bias [18,[20][21][22]25] were unclear in a number of studies. While blinding was used in only 2 studies [17,18], likely due to difficulties in concealment of the different fluid regimens and/or haemodynamic monitoring technologies employed, strict protocolisation of fluid and diuretic use was felt to ameliorate the effects of this potential bias in all but two studies [19,21].…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of random sequence generation and allocation concealment [19][20][21][22]25] and the risk of reporting bias [18,[20][21][22]25] were unclear in a number of studies. While blinding was used in only 2 studies [17,18], likely due to difficulties in concealment of the different fluid regimens and/or haemodynamic monitoring technologies employed, strict protocolisation of fluid and diuretic use was felt to ameliorate the effects of this potential bias in all but two studies [19,21].…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
“…We found increased VFDs with a conservative or deresuscitative fluid strategy in comparison with a liberal strategy or standard care (mean difference 1.82 days [95% CI interval 0.53 to 3.10 days], I 2 =9%). In addition, studies by Hu et al [21] and Wang et al [22] reported shorter duration of mechanical ventilation in a more conservative fluid strategy group compared with the liberal fluid strategy group (10.13 +/-3.02 days vs. 12.64 +/-2.89, P<0.05 and 9.62 +/-2.55 days vs 12.51 +/-2.92 days, P<0.05 respectively).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations